Analisis Kompensasi Karyawan Bagian Packaging Section PT Astra Honda Motor Part Center Karawang - Setiyawan, Iman; Fadli, Uus Mohammad Darul (LANCAH: Jurnal Inovasi dan Tren, 2024)
One of the best strategies for improving HR performance and achieving company goals is to guarantee compensation for employee welfare. This research aims to analyze forms of compensation, both monetary and non-monetary compensation, and examine whether compensation can influence employee performance. The research used is a qualitative type of research. The research focus is employees of the Packaging Section of PT Astra Honda Motor Part Center, Karawang, West Java, Indonesia. The informants from this research were 6 people, including 1 leader, 1 permanent employee and 4 contract employees. Primary data regarding the compensation system used at PT Astra Honda Motor Karawang was obtained through direct interviews with the Production Leader and several contract employees representing the Packaging Section. Documents from the company such as company profiles, company history, and collective bargaining agreements are used as secondary data in this research. The results of this research show that compensation plays an important role in improving employee performance through the motivation generated in each individual and their contribution to achieving organizational goals.